USM KNOWLEDGE TRANSFER PROGRAMME (KTP) RECEIVED PRESTIGIOUS MELAKA GREEN AWARD 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
MELAKA, 13 August 2016 Universiti Sains Malaysia (USM) Knowledge Transfer Programme (KTP) is proud to have been awarded the Melaka Green Award 2016 for academic collaborations in a ceremony held here yesterday.